HPLC Method for the Estimation of Albendazole in Pharmaceutical Dosage Forms - Krishnaiah, Y.S.R.; Latha, K.; Karthikeyan, R.S.; Satyanarayana, V. (Asian Journal of Chemistry, 2010)
A reverse phase high-pressure liquid chromatographic method (HPLC) has been described for the estimation of albendazole in its tablet dosage form using RP C-18 column. The mobile phase consisted of acetonitrile and water (containing 0.4% triethylamine adjusted to pH 3.6 with 5% orthophosphoric acid) in the ratio of 46 : 54. Mebendazole was used as internal standard. The detection was carried out at 254 nm and the linearity was found to be in the range of 0.1 to 40 μg/mL. The method is simple, precise, specific, less time-consuming and accurate for the estimation of albendazole in tablet dosage forms.